EVALUATION OF TECHNICAL EFFICIENCY OF THE HOTEL SECTOR AND CAMPSITES IN SPAIN (Dimensión Empresarial, 2016)
Tourism has a multiple sectors and a dynamic nature, attached to economy during and after the service. These links are particularly important in order to approach the development of a country and, specially, tourism. In this context, technical efficiency of hotels, hostels and Spanish camping are analyzed. More specifically, the approach of the stochastic boundary is going to be followed in order to assess the level of efficiency and the relative weight of hotels, hostels and campsite in economy. This study also assesses each region’s technical efficiency, the relationship between tourism merchant society’s typology and technical efficiency. This document assesses the development of 212 firms, which work on CNAE-2009 activity 55’s sector between 2011 and 2012. Due to the results obtained, we can affirm that the efficiency level of Spanish hotel’s sector is high, more competitive and efficient every year.
Keywords: Eficiencia Técnica; actividad turística; hoteles y campings; España.